Packet monitoring and filtering for network intrusion detection system (NIDS) - Mohd Faez, Muzamel (Universiti Malaysia Sarawak (UNIMAS), 2005)
This proposed project is preliminary development on the project of Network Intrusion Detection Systems (NIDS). After discovery several existing network security system, it can indicated that these system still have weaknesses. Therefore, this proposed project will attempt to present some issues that can heal the existing weaknesses. It not a good practical if we rely on one security layer such as only put the firewall system. Studies the other method of security system is compulsory in order to fulfil the requirement of network security. In this proposed project, Network Intrusion Detection System has been choosing as a support for the network security.